Pengaruh Menonton Iklan Web Series Versi "Jejak Rasa" Di Youtube Terhadap Minat Beli Produk Eiger - Faisal Reza (ArtComm, 2019)
The Series' trail is a series of web series advertisements created by outdoor equipment products uploaded by Eiger Adventure Indonesia's official Youtube account. Youtube is one of the most common social media platforms accessed by the people of Indonesia. This research is a quantitative study using a survey method with data analysis techniques calculated using SPSS 25 software with skewnes and kurtosis techniques, Pearson correlation coefficient and simple linear regression. Based on the results of the study, the value of the relationship between variables is (0.575) and the value (R) or correlation is (0.591). Through this value it is also known that the value of (R Square) or the coefficient of determination is (0.349) which means there is an influence from watching the web series advertisement version of "Imprint" on Youtube to the buying interest of Eiger products by 34.9% or included in the relationship category " Medium ".